Jarchas: una propuesta de armado textual (2015)
This is a playful, experimental and daring stake, from a historical, discursive and creative way. A historical tour of medieval erotic texts is constructed to flow into a particular poetic love expressions by words. Finally, we have taken some kharjas from the corpus of the Ibn Colin Busra Manuscript (Barmatán, 1974), whose original sequence is haphazard; we ordered a possible text like a palimpsest, in our case as an inquiry and recreation exercise.